EFEKTIVITAS PELATIHAN “PERAN ORANG TUA DALAM MENDAMPINGI PENGGUNAAN GADGET ANAK” TERHADAP POLA INTERAKSI ORANG TUA-ANAK - Hidayat, Dyah Aji Jaya (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2022)
The use of gadgets that are less controlled among children causes anxiety for parents. It not only affects the academic value and personality of the child, but also on the interaction pattern of parents and children. This study aims to determine the effectiveness of the "The Role of Parents in Assisting Children's Gadget Use" training on parent-child interactions. The research method used is a quantitative experiment with a one group before-after experimental design. The training program is given to parents for one session with a duration of 120 minutes. The subjects of this study were parents aged 25-40 years and had children aged 5-12 years living in Dukuh Tanggan, Gesi, Sragen. The research sample is 15 people. The data collection in this study used a scale of parent-child interaction patterns. The hypothesis test used is Paired Samples T-Test with a pretest mean of 87.40 and a post-test mean of 93.33, with a t value of -1,347 and sig. (2 tailed) = 0.035. Thus, this training was able to significantly improve the pattern of parent-child interaction.